2022
DOI: 10.3390/diseases10040085
|View full text |Cite
|
Sign up to set email alerts
|

Luspatercept: A New Tool for the Treatment of Anemia Related to β-Thalassemia, Myelodysplastic Syndromes and Primary Myelofibrosis

Abstract: Anemia is a common feature of both benign and malignant hematologic diseases. Beta-thalassemia (β-thalassemia) syndromes are a group of hereditary disorders characterized by ineffective erythropoiesis, due to a genetic deficiency in the synthesis of the beta chains of hemoglobin, often accompanied by severe anemia and the need for red blood cell (RBC) transfusions. Myelodysplastic syndromes (MDS) are characterized by cytopenia(s) and ineffective hematopoiesis, despite a hypercellular bone marrow. Primary myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…19 It was also noted by Taher and colleagues 20 that patients with thalassemia intermedia also show an increased risk of thrombotic/thromboembolic events, especially those who had splenectomies. Although it is advised to start thromboprophylaxis if patients with splenectomy start on luspatercept, 21 our patient was reluctant and refused to start due to fears of aspirin side effects. Her course after starting treatment was uneventful from a thrombotic events point of view.…”
Section: Discussionmentioning
confidence: 84%
“…19 It was also noted by Taher and colleagues 20 that patients with thalassemia intermedia also show an increased risk of thrombotic/thromboembolic events, especially those who had splenectomies. Although it is advised to start thromboprophylaxis if patients with splenectomy start on luspatercept, 21 our patient was reluctant and refused to start due to fears of aspirin side effects. Her course after starting treatment was uneventful from a thrombotic events point of view.…”
Section: Discussionmentioning
confidence: 84%
“…Luspatercept, a recombinant fusion protein that decreases SMAD2/3 signaling, promotes erythroid maturation and improves anemia. Luspatercept was approved as a treatment for anemia in patients with very low- to intermediate-risk myelodysplastic syndromes (MDS) with ring sideroblasts or MDS/MPN with ring sideroblasts and thrombocytosis (April 2020); lower-risk MDS and requirement for RBC transfusions (August 2023); and β-thalassemia with necessity for RBC transfusions (November 2019) [ 99 ]. Future treatments of MF patients with anemia may include regimens combining luspatercept with JAK inhibitors.…”
Section: Tgf-β Ligand Traps As Treatments For Anemiamentioning
confidence: 99%
“…Notably, retrospective analyses demonstrated that momelotinib maintained its efficacy in thrombocytopenic patients in the two SIMPLIFY-1 and SIMPLIFY-2 trials [140] as well as in the MOMENTUM trial (Table 2) [136,141]. Luspatercept (activin receptor-ligand trap enhancing late-stage erythropoiesis [142]) was evaluated in MF patients with anemia in a phase 2 trial (NCT03194542): in Cohort 3B (transfusion-dependent patients on a stable dose of ruxolitinib), RBC transfusionindependence was achieved in 27% and 36% of the patients, respectively, over any the entire treatment period was assessed; RBC transfusion burden decreased by ≥50% over at least 12 weeks in 46% of the patients [143]. At present, luspatercept is being evaluated in the registrational, phase 3 trial INDEPENDENCE (NCT04717414) in MF patients who are receiving a stable dose of a JAK inhibitor and require RBC transfusions [144].…”
Section: Phenotypes Molecular Profiles and Differentiated Efficacy Of...mentioning
confidence: 99%